SISTEM PENGENDALIAN MANAJEMEN LINTAS BUDAYA: STUDI KASUSPADARESTORAN “T”DI SURABAYA - Felicia Lianggara; Bonnie Soeherman (CALYPTRA, 2018)
This study was made to look at management control systems, acculturation, and cross-cultural communication barriers that appear in Restaurant "T". Cultural differences that exist This research is included in the basic research. The writer hopes this research can provide a picture about the cultural differences between Korean owners and local staffs. The research methods are interview,observation and document analysis.Cultural acculturation between owners with Korean citizenship and Indonesian citizenship takes place in the "T" Restaurant. The existence of some cultural differences also causing the owner to adapt to the local culture that surrounds them.